One-Pot Three-Component Coupling Reaction of α-Amino Aryl Ketones, Indoles, and Perbromomethane Under Mild Conditions - Chen, De; Lu, Hao; Liu, Yuxuan; Deng, Wei; Qiu, Renhua; Xiang, Jiannan (Frontiers in Chemistry, 2022)
A simple and efficient one-pot three-component cascade reaction of α-amino carbonyl compounds, indoles and CBr4 in moderate to good yields has been developed. This new strategy exhibits excellent mild reaction conditions and step-economy, easily accessible reactiants and simultaneous construction of three different new bonds (C=N, C–C, and N-Br) in a single step. It is worth noting that the protocol developed provides a simple and practical tool for the construction of diverse indole-containing heterocyclic frameworks, indicating its potential applications in medicinal and material chemistry.